2015
DOI: 10.1139/cjb-2014-0210
|View full text |Cite
|
Sign up to set email alerts
|

A CYCLOIDEA-like gene mutation in sunflower determines an unusual floret type able to produce filled achenes at the periphery of the pseudanthium

Abstract: The pseudanthium of sunflower (Helianthus annuus L.) consists of two floret types: zygomorphic sterile ray florets and\ud actinomorphic hermaphrodite disc florets. In the tubular ray flower (turf) mutant, the loss-of-function of a CYCLOIDEA (CYC) gene\ud generates hermaphrodite tubular-like ray florets that replace the normal sterile ray florets. We evaluated whether tubular-like\ud ray florets have a multifaceted set of floral traits and the presence of heteromorphic seeds in the turf inflorescence. During ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…There have been some reports of floral organ regulation in the Compositae. For example, some studies have shown that CYC-like genes play an important role in the symmetry of ray floret in members of the Compositae (Chapman et al, 2012;Juntheikki-Palovaara et al, 2014;Liu et al, 2016;Mizzotti et al, 2015). Ray floret architecture in chrysanthemum may range from a flat type (lateral symmetry) to tubular type (radial symmetry), and we found that there are many intermediate states between these extremes, suggesting that this is quantitative character.…”
Section: Discussionsupporting
confidence: 55%
“…There have been some reports of floral organ regulation in the Compositae. For example, some studies have shown that CYC-like genes play an important role in the symmetry of ray floret in members of the Compositae (Chapman et al, 2012;Juntheikki-Palovaara et al, 2014;Liu et al, 2016;Mizzotti et al, 2015). Ray floret architecture in chrysanthemum may range from a flat type (lateral symmetry) to tubular type (radial symmetry), and we found that there are many intermediate states between these extremes, suggesting that this is quantitative character.…”
Section: Discussionsupporting
confidence: 55%
“…The high number of anther/flower in ray‐like flowers might be a related to the origin of these flowers from hermaphrodite actinomorphic disc flowers (Mizzotti et al . ). The presence of anther and styles also in true ray flowers (Table , Fig.…”
Section: Resultsmentioning
confidence: 97%
“…; Mizzotti et al . ). In addition, the incomplete filaments attached at the base of the corolla tube of ray flowers of sunflower are likely a remnant of ancestral stamens.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, some researchers have suggested that the petal type of Compositae species shows a change from bilateral asymmetry (flat type) to radial symmetry (tubular type). Therefore, researchers have focused on genes related to floral symmetry, such as the CYC-like gene 41,42 . However, our study suggests that many intermediate types exist between the flat and tubular types in chrysanthemum, which means that the variation in petal type (redefined in our study as CTMD) is partly determined by floral symmetry.…”
Section: Inheritance Mode In Chrysanthemummentioning
confidence: 99%